Electro-capacitive cancer therapy using wearable electric field detector: a review - Tole Sutikno; Fadlil Fadlil; Ardiansyah Ardiansyah; Warsito P Taruno; Lina Handayani (Computer Science and Information Technologies, 2024)
Electro-capacitive cancer therapy (ECCT), a less invasive and more targeted approach using wearable electric field detectors, is revolutionizing cancer therapy, a complex process involving traditional methods like surgery, chemotherapy, and radiation. The review aims to investigate the safety and efficacy of electric field exposure in vital organs, particularly in cancer therapy, to improve medical advancements. It will investigate the impact on cytokines and insulation integrity, as well as contribute to improving diagnostic techniques and safety measures in medical and engineering fields. Wearable electric field detectors have revolutionized cancer therapy by offering a non-invasive and personalized approach to treatment. These devices, such as smart caps or patches, measure changes in electric fields by detecting capacitance alterations. Their lightweight, comfortable, and easy to-wear nature allows for real-time monitoring, providing valuable data for personalized treatment plans. The portability of wearable detectors allows for long-term surveillance outside clinical settings, increasing therapy efficacy. The ability to collect data over extended periods provides a comprehensive view of electric field dynamics, aiding researchers in understanding tumor growth and progression. Technology advancements in electro-capacitive therapy, including wearable devices, have revolutionized cancer treatment by adjusting electric field intensity in real-time, enhancing personalized medicine, and improving treatment outcomes and patient quality of life.